Quantum Optical Properties of Nanowire Quantum Dots - Laferrière, Patrick (Université d'Ottawa / University of Ottawa, 2023)
Ideal sources of single-photons are required for proposed applications in quantum information technologies, such as quantum cryptography, and linear optical quantum computing. Quantum dots have become one of the most promising candidates for the generation of ideal single-photons due to its low multi-photon emission probability, entangled pair generation with high fidelity, and can be generated on-demand. The most common quantum dots studied are self-assembled quantum dots which nucleate on a surface in a random nature providing a series of dots randomly positioned and of random sizes. Much work has been done to achieve high extraction efficiencies by creating different photonic structures around these quantum dots. This work investigates the quantum optical properties of Indium Arsenide Phosphide (InAsP) quantum dots embedded within Indium Phosphide (InP) nanowire photonic waveguides grown bottom-up using selective-area vapour-liquid-solid epitaxy. These structures provide full control over the quantum dot size, composition, and its position along the nanowire waveguide axis. We characterize the sources in terms of their efficiencies, single-photon purity, and spectral purity. We show that our devices operate at efficiencies up to 30% with a single-photon purity as high as 99.4% and can reach linewidths that are twice the lifetime limited value, unprecedented for the above-band excitation scheme employed. Studies of the second-order auto- and cross-correlations of the nanowire quantum dots is provided, which shows rich temporal features. We show that different excitonic complexes exhibit different correlation spectra and are unique to each complex. The study of cross-correlation measurements provided an unbiased, accurate method to distinguish and identify different complexes emitted by the quantum dots. A stochastic model is provided to model auto-correlation measurements which highlight the complex nature of the carrier dynamics within nanowire quantum dots. Such studies are a step closer to the full understanding of the dot dynamics within nanowire waveguides. An interesting consequence of growing nanowires using the bottom-up epitaxial growth method is that quantum dots can be selectively positioned within the core of the nanowire waveguide. Such selectivity, along with wavelength tuning of the quantum dots, allows for the incorporation of multiple quantum dots within the same nanowire waveguide emitting at specific wavelengths. We show that the total single-photon emission rate scales linearly with the number of incorporated emitters whilst maintaining a high single-photon purity. The total emission rate of such wavelength multiplexed sources would then be limited only by the number of emitters, providing a route towards GHz emission rates. Finally, a new growth approach to generate single-photons at telecom wavelengths is investigated: the dot-in-a-rod embedded in a photonic nanowire waveguide. We demonstrate that this new growth approach provides efficient and highly pure single-photons at telecom wavelengths operating at 4K. We then investigate the single-photon purity as a function of temperature up to room temperature. The results at elevated temperatures are shown to outperform all other existing quantum dot based approaches at telecom wavelengths.
Keywords: Single-photons; Nanowire; Quantum dot